Joint torque evaluation of lower limbs in bicycle pedaling - Yamazaki, H.; Matsuda, A. (Procedia Engineering, 2016)
In this paper, joint torque powers of lower limbs in bicycle pedaling were investigated numerically. An approximation method of relationship between the angle of the ankle and normal force in the rotation direction of a bicycle crank while pedaling was investigated